Sustainable use of water resource at North Kendeng Mountain, Central Java, Indonesia. (October 2018) - Hadi, S P; Purnaweni, H; Hadiyanto,; Prabawani, B
Abstract: Conflict between local community on one side, and government and private sector on the other side over the utilization of limestone at North Kendeng Mountain area, Central Java, Indonesia has been occurred since 2008. The government prefers to utilize limestone for mining in order to create economic growth, job opportunities and other positive impacts. Local community are worried about mining activities which will potentially deplete water resources currently being utilized for household use and irrigation for rice production. Strategic Environmental Assessment (SEA) is expected to mediate conflict by recommending on the allocation of areas for conservation and for mining. SEA found that the demand of water at research area has been exceeded the availability of water due to increase of population, government policies and planned activities of cement factories. Institutional and substantial arrangements are required to create a sustainable use of water resources.